Lifestyle-related Health Problems Confronting Japanese-Brazilians Immigrated to Japan - FUKUSHIMA, Tetsuhito; MORIYAMA, Masaki (JOURNAL OF THE JAPANESE ASSOCIATION OF RURAL MEDICINE, 2003)
To clarify the relation between living habitudes in Japan including daily fare and health, the state of health of 21 Japanese-Brazilians living in Japan was investigated. The relation was analyzed based on their views, about the Japanese customs. Only two persons were found to have adapted themselves to the living environment in Japan, 10 persons were not adaptable sufficiently and 9 suffered from maladaptation. Asked why they were not adaptable, they gave personal relations, difficulty in reading and writing, workplace stress, etc. It was also found that at the present their biggest worry concerned the future, followed by personal relations, Japanese language, work and education in that order. Our investigation brought to light the fact that there was much to be done by the local community in terms of receiving immigrants. When it came to foodstuffs, after visiting Japan, the intake of salt, meat and fruit decreased, and fish increased. Like most Japanese, the Japanese-Brazilians regarded salad and rice-baseddiet healthy, but coffee not good. Referring to some foodstuffs which are customarily eaten less, many said they feel eating a lot of fish and shellfish in Japan is good for the health, but little fruit and little bean food are not good. As for the present health condition, more than half of the subjects said they had some problem. In the relation between the change in weight and the change in eating habit, only the increased intake of sugar was related to weight gain. The effect of the Japanese way of life on their health must be continuously followed up on with the common and different points of the customs in eating between Brazil and Japan taken into account.